Concomitant continuous pain in patients with trigeminal neuralgia is associated with trigeminal nerve root atrophy. (November 2020) - Di Stefano, Giulia; De Stefano, Gianfranco; Leone, Caterina; Cruccu, Giorgio; Tardioli, Stefano; Cartocci, Gaia; Fiorelli, Marco; Truini, Andrea; Caramia, Francesca
Introduction: Trigeminal neuralgia is an exemplary neuropathic pain condition characterized by paroxysmal electric-shock-like pain. However, up to 50% of patients also experiences concomitant continuous pain. In this neuroimaging study, we aimed to identify the specific anatomical features of trigeminal nerve root in patients with concomitant continuous pain. Methods: We enrolled 73 patients with a definitive diagnosis of classical and idiopathic trigeminal neuralgia and 40 healthy participants. The diagnosis of trigeminal neuralgia was independently confirmed by two clinicians. Patients were grouped as patients with purely paroxysmal pain (45 patients) and patients also with concomitant continuous pain (28 patients). All participants underwent a structured clinical examination and a 3T MRI with sequences dedicated to the anatomical study of the trigeminal nerve root, including volumetric study. Images analysis was independently performed by two investigators, blinded to any clinical data. Results: In most patients with concomitant continuous pain, this type of pain, described as burning, throbbing or aching, manifested at the disease onset. Demographic and clinical variables did not differ between the two groups of patients; the frequency of neurovascular compression and nerve dislocation were similar. Conversely, trigeminal nerve root atrophy was more severe in patients with concomitant continuous pain than in those with purely paroxysmal pain ( p  = 0.006). Conclusions: Our clinical and neuroimaging study found that in patients with trigeminal neuralgia, concomitant continuous pain was associated with trigeminal nerve root atrophy, therefore suggesting that this type of pain is likely related to axonal loss and abnormal activity in denervated trigeminal second-order neurons.